Differences in welfare take-up between immigrants and natives - Kerstin Bruckmeier; Jürgen Wiemers (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
Research on welfare participation often shows significant differences between immigrants and natives that are often attributed to immigrants' higher risk of welfare dependence. We study whether immigrants in Germany also differ from their German counterparts in their take-up behavior conditional on being eligible for welfare benefits. The empirical approach intends (i) to determine eligibility for welfare benefits for a representative sample of the whole population of Germany using a microsimulation model (IAB-STSM) based on data from the German Socio-Economic Panel (GSOEP) and then (ii) to estimate probit models of observed welfare benefit take-up for the sample of eligible households. Our simulation results show that non take-up rates do not differ significantly between several groups of immigrants and natives. Additionally, the probit estimations do not reveal a significant effect of being a migrant on the probability to take up entitlements. Hence, our findings suggest that after controlling for observed and unobserved household characteristics immigrants are not more prone to take up welfare benefits.
Keywords: I38; H31; C15; 330